Metamorphism in the A Vuong Formation, southern Truong Son Belt, Vietnam - Vuong Bui Thi, Sinh; Kitano, Ippei; Tran, Tuan-Anh; Pham-Ngoc, Can; Vu Hoang, Ly; Pham Thi Phuong, Lien; Ngo Thi, Huong; Tran Quoc, Cong (Vietnam Journal of Earth Sciences, 2025)
The A Vuong Formation, located within the southern Truong Son Belt in central Vietnam, comprises low- to high-grade metamorphic rocks that record crucial insights into the region’s tectonic evolution. Our field investigations reveal that it mainly consists of the psammitic and pelitic schists, intercalated with some mafic or siliceous layers, and locally cut by leucocratic veins. The indicative mineral assemblages in the pelitic to psammitic schists define two metamorphic zones: a greenschist-facies biotite-chlorite zone and an amphibolite-facies staurolite zone. Based on conventional geothermobarometry, the peak metamorphic condition in the staurolite zone was estimated at ca. 5.5–8.7 kbar and 590–640℃, followed by a retrograde stage at 4.4–7.4 kbar and 530–570℃. Notably, a porphyroblastic andalusite observed in a pelitic schist from this zone is rimmed by kyanite with a preferred orientation. In addition, it includes kyanite, sillimanite, and an intergrowth of staurolite + quartz as inclusions. These features suggest their equilibrium during the prograde stage, reflecting a pressure-temperature transition from andalusite to kyanite stability. The prograde metamorphic condition is thus constrained at the triple point of andalusite-kyanite-sillimanite. The petrological evidence and estimated metamorphic conditions for the current pelitic schists support a unique anti-clockwise pressure-temperature trajectory, rather than a clockwise one. Its thermobaric feature is well aligned with the amphibolite-facies metamorphism of the neighboring Dai Loc Complex, and contrasts with that of the Kham Duc Complex (Kontum Massif).